PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, KOMITE AUDIT, DAN KLASIFIKASI INDUSTRI TERHADAP AUDIT DELAY (STUDI EMPIRIS PADA CONSUMER GOODS INDUSTRY DAN PERBANKAN) - Firdani, Fanni; Widyastuti, Tri; Supriyadi, Edy (SEKOLAH PASCASARJANA PRESS, 2019)
The purpose of this research is to analyze and obtain empirical evidence related to the influence of company size, company age, audit committee, and industry classification on audit delay simultaneously and partially. This research method uses a quantitative approach using 163 samples of companies in the Consumer Goods and Banking sector collected from the Indonesia Stock Exchange (IDX) for the period 2014-2016 as research material. The results of this study found that firm size and industry classification had a significant negative effect on audit delay, the audit committee had a significant positive effect on audit delay while the age of the company had no significant effect on audit delay.